Density functional tight-binding study of li-intercalation in B-MnO2 for lithium-ion batteries - Ngobeni, Percy (My University, 2022)
The derivation of β-MnO2 potentials was carried out using self-consistent density functional tight-binding (SSC-DFTB) parameterization within Material Studio®. For exchange-correlation functional, the generalized gradient approximation (GGA) was used in the form of PBE exchange-correlation functional during parameterization. Dmol3 is a density functional theory-based program that is used to calculate the lattice parameter of ferromagnetic β-MnO2. The potentials were used in the investigation of the structural and electronic properties of β-MnO2. After successfully parameterizing β-MnO2, the lattice parameters were compared with the results from experiments and Density Functional Theory. Density functional tight-binding (DFTB) was employed to investigate the electronic properties of β-MnO2 such as density of states (DOS) and band structures. The DOS was calculated to check the nature of the investigated system. The electronic band structures calculated were also to confirm the results of the DOS since they go hand in hand. We further employed the Density Functional Theory to investigate the surfaces (110) of β-MnO2, β-TiO2, and β-VO2 which act as catalysts in Li/Na-air batteries. We investigated the electronic properties of metal oxides β-MnO2, β-TiO2, and β-VO2 (MO2) which are used as a catalyst in metal-air batteries. Electronic properties of MO; MnO2, TiO2, and VO2 were determined by looking at the tetragonal structure. However, further investigations of the electronic properties of oxygen adsorption Li/MO2 and Na/MO2 (110) surfaces in metal-air batteries.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2022
Keywords: Density functional; Li-intercalation; Lithium-ion Batteries; Lithium ion batteries; Density functionals; Electronic properties